Evaluating Distributive Fairness of Remuneration System: The Role of Equity Sensitivity in Explaining Employee Well-being and Organizational Citizenship Behaviour - Elsa Sari Yuliana; Sari Zawitri; Widodo PS; Theresia Siwi Kartikawati (Jurnal Manajemen Industri dan Logistik, 2022)
This study aims to test the effect of remuneration system fairness on subjective well-being and OCB. This research also aims to test the moderating role of equity sensitivity in the effect of remuneration system fairness on subjective well-being. The technique of sample collection employed purposive sampling technique. The hypothesis testing employed path coefficient value and t-test using SmartPLS 3.0. In accordance with the test results show that in the context of public universities in Indonesia, namely PU, employee OCB is influenced by the remuneration system variable and subjective welfare variable. This study also concludes that subjective well-being is a mediator between the two. On the other hand, the moderating role of equity sensitivity in the effect of fairness remuneration on subjective well-being is not well-proven. Theoretically, this research provides generalization to the previous studies, as well as complementing the need for balancing mediator and moderator variables in the correlation between remuneration system fairness and OCB. Practically, this study denotes that organizations need to take concern about fairness in the regulations of remuneration system.